Microbiological and physicochemical properties of commercial seal tampered refrigerated fruit juices - Oluwole, Olusola; David, Oluwole; Falegan, christopher; Awojuyigbe, Biodun; Olajide, Olatunji (International Journal of Biological Research, 2016)
Microbial and physicochemical properties of seven branded, seal tampered refrigerated fruit juices were carried out in this study using standard methods. Coliform counts ranged from 2.079 to3.093 log10cfu/ml over the storage period with pineapple juice and citrus juice having the highest and least coliform count respectively. Total bacteria count in the juice ranged from 7.009 to 8.243 log10cfu/ml. Citrus fruit juice however had the highest staphylococcal count while pineapple juice had the least (2.344 to 3.881log10cfu/ml). Also, osmophilic yeast count ranged from 2.017 to 3.903log10cfu/ml, having the highest load in orange fruit juice and lowest load in citrus fruit juice. The pH of the juice samples ranged from 2.9 to 4.2 during the period of refrigeration. Conductivity was highest in apple fruit juice and lowest in orange nectar pulp fruit juice. The total dissolved solids ranged from 0.29 to 1.95 over storage and was recorded highest in apple juice and lowest in orange nectar pulp fruit juice. Turbidity ranged from 5.8-200. These results indicate a reduction in the quality of fruit juices after 5 days of opening and thus reveals that both spoilage and pathogenic organisms could proliferate in juices despite refrigeration.